Maternal chocolate and sucrose soft drink intake induces hepatic steatosis in rat offspring associated with altered lipid gene expression profile. (12th July 2013) - Kjaergaard, M.; Nilsson, C.; Rosendal, A.; Nielsen, M. O.; Raun, K.
Abstract Aim According to the World Diabetes Foundation, there is an urgent need to investigate the impact of maternal health and nutrition during pregnancy to understand the background for the accelerating incidence of obesity and type 2 diabetes. In this study, we specifically concentrated on the role of overfeeding during different developmental periods. Methods Sprague–Dawley rats were offered chow or high‐fat/high‐sucrose diet (chow plus chocolate and soft drink) during gestation and lactation. At birth, offspring were randomly cross‐fostered within each dietary group into small and normal litter sizes until weaning, giving four dietary groups. Results At postnatal day 1, offspring from high‐fat/high‐sucrose‐fed dams were heavier and had increased hepatic triglycerides (TG), hepatic glycogen, blood glucose and plasma insulin compared with offspring from chow‐fed dams. Hepatic genes involved in lipid oxidation, VLDL transport and insulin receptor were down‐regulated, whereas FGF21 expression was up‐regulated. Independent of postnatal litter size, offspring from high‐fat/high‐sucrose‐fed dams aged 21 days had still increased hepatic TG and up‐regulated FGF21 expression, while plasma insulin started to decrease. Litter size reduction in offspring from high‐fat/high‐sucrose‐fed dams further increased body weight and adiposity, and up‐regulated genes involved in hepatic mitochondrial lipid oxidation and VLDL transport compared with all other groups. Litter size reduction did not have any impact on body weight gain and adiposity in offspring born to chow‐fed dams. Conclusion Our results suggest that supplementation of chocolate and soft drink during gestation and lactation contributes to early onset of hepatic steatosis associated with changes in hepatic gene expression and lipid handling.